Control interno y gestión de tesorería en la unidad ejecutora de salud Ucayali Contamana 2024 - Orbe Flores, Saori Adalgisa (2024)
The primary objective of the study was to determine the relationship between internal control and treasury management in the Health Execution Unit Ucayali Contamana for the year 2024. This research was characterized as being of a basic type, at a descriptive and correlational level, and was developed under a non-experimental design. A sample of 80 workers was selected, to whom a questionnaire was applied for data collection. Subsequently, the data were processed using Excel and SPSS programs, according to the needs of the study. It was concluded that internal control is perceived as regular (25%) and adequate (23%), with aspects such as procedure and supervision/monitoring being more effective, while human resources and organization require improvements. Treasury management varied between regular (25%) and very efficient (20%), with mixed evaluations in fund administration and spending execution procedures. A strong positive correlation (Spearman coefficient of 0.750) was found between internal control and treasury management, corroborated statistically significant (Sig. = 0.000), indicating that improvements in one could positively influence the other.